2022
DOI: 10.1111/dth.15814
|View full text |Cite
|
Sign up to set email alerts
|

New onset atopic dermatitis and psoriasis in the same patients under biologic treatments: The role of systemic treatments as a possible trigger

Abstract: Atopic dermatitis (AD) and psoriasis (PsO) are among the most common diseases in the daily clinical practice. Usually, AD and PsO are reported as two diseases that cannot coexist in the same patient because this requires the activation of opposing inflammatory pathways. Anyway, some reports highlight how AD and PsO may coexist in the same patient or develop consequently. In this short report we collected 12 patients that developed new AD or PsO. Among them, eight patients (n = 8; 3M:5F) with a previous diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
0
7
0
1
Order By: Relevance
“…Recently, some studies have highlighted that AD and psoriasis may coexist in the same patient or develop consequently [ 15 ]. The mechanisms by which AD patients develop psoriasis or psoriatic patients develop AD are still not very clear, and some triggers such as biologics therapy can promote these processes [ 16 ]. Our research identified hub genes that help us better understand the pathogenesis of AD and psoriasis, and may aid in the development of certain biomarkers for diagnosing AD and psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some studies have highlighted that AD and psoriasis may coexist in the same patient or develop consequently [ 15 ]. The mechanisms by which AD patients develop psoriasis or psoriatic patients develop AD are still not very clear, and some triggers such as biologics therapy can promote these processes [ 16 ]. Our research identified hub genes that help us better understand the pathogenesis of AD and psoriasis, and may aid in the development of certain biomarkers for diagnosing AD and psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep disorders and an unhealthy lifestyle, such as the western dietary pattern, negatively impinge on skin homeostasis and regulate or exacerbate the development, clinical course and outcomes of PsO [ 157 , 158 ]. Indeed, both factors and PsO disease have in common an alteration of immune-mediated responses and chronic inflammatory conditions [ 159 , 160 ]. Remarkably, exposure to other factors, such as alcohol, infections, vaccines, pollution and smoking, may also influence the patient course and modulate sleep quality, so together with the diet, clinicians should advocate a change in the patient’s lifestyle [ 161 , 162 , 163 , 164 , 165 , 166 ].…”
Section: Discussionmentioning
confidence: 99%
“…Four small case series were identified reporting data on a total of 16 patients whose details are reported in Table 1 [5][6][7][8]. One additional manuscript reported a case of a dupilumabtreated patient who developed new-onset psoriasis, but the type of biologic prescribed for psoriasis, the duration of the treatment, the age and gender of the patient were missing in the full text of the manuscript [9], so that we could not include this case in our analysis. To these patients, we have added other original patients (n = 8) derived from our clinical practice, achieving a total of 24 cases followed for a period of 2-22 months.…”
Section: Key Summary Pointsmentioning
confidence: 99%